Factors Contributed to the Development of Work Engagement among Nurses in the Hospital: Narrative Review - Elis Rahmawati; Hana Rizmadewi Agustina; Kurniawan Yudianto (Universitas Padjadjaran, 2022)
Engagement is a characteristic of an employee who is committed to the organization. An engaged nurse shows strong work dedication and works productively in advancing the hospital organization. Nurses with good work engagement can improve the quality of nursing in the hospital. This study aims to determine the factors that influence nurses' work engagement to serve as a knowledge base to guide the best practice of nursing services. This study used a narrative review design. This review starts by identifying the main topics in work engagement. This study used narrative review, a method that uses four databases namely PubMed, CINAHL, Google Scholar and ProQuest. Inclusion criteria included full text articles and publications in English and Indonesian between 2015-2021. The study found 13 articles. Several factors were found to influence nurses' work engagement both from within and from outside (motivation, moral competition, supervision and others).